COVID-19 Keep calm and carry on learning: using Microsoft Teams to deliver a medical education programme during the COVID-19 pandemic. Issue 3 (2020) - Henderson, Daisy; Woodcock, Hannah; Mehta, Jay; Khan, Nuzhath; Shivji, Victoria; Richardson, Charlotte; Aya, Haleema; Ziser, Shier; Pollara, Gabriele; Burns, Aine
No abstract available